Addressing the Gender Gap: Using Quantitative and Qualitative Methods to Illuminate Women’s Fisheries Participation - Szymkowiak, Marysia; Rhodes-Reese, Melissa (Frontiers in Marine Science, 2020)
While key to the sustainability of fisheries, women’s contributions to this sector are largely outside of the conventional discourse on fisheries participation and remain poorly understood and unrecognized. Furthermore, the research on women’s engagement in fisheries has largely focused on small-scale fisheries in a development context. This study extends this geographic focus by using a systematic analysis of the literature to explore how women’s fisheries participation has been examined in developed countries in Europe and North America. We demonstrate the preponderance of themes and methodologies that have been utilized in these regions, highlighting the reliance on case studies employing qualitative methods due in part to the dearth of gender disaggregated data in this sector. Although such methods can yield a deep understanding, the results are often limited in geographic scope and generalizability. In response, we present a methodological approach that can extend the scope of research and comprehensively examine women’s participation across its multifaceted dimensions. We demonstrate the accuracy of a freely available software to predict gender using limited personal information and apply it to harvest data in Alaska, addressing the previous impediment of a lack of a gender attribute within fisheries datasets and extending the methodological applications to include quantitative methods. This is coupled with focus groups across highly engaged fishing communities in the Gulf of Alaska to integrate the multiple themes that have been explored in the literature on women’s fisheries participation, evidencing the utility of a mixed-methods approach to explore the multi-faceted nature of women’s fisheries engagement.